PREREQUISITES FOR EARLY PREGNANCY LOSS IN WOMEN WITH CHRONIC ENDOMETRITIS - В. Ліхачов; О. Тарановська; І. Жабченко; В. Оксюта; В. Палапа; Е. Крутікова (Bukovynian State Medical University, 2024)
The incidence of chronic endometritis is particularly high in women with spontaneous abortions, especially habitual ones. There are insuffi cient data on the mechanisms of miscarriage in women whose pregnancy occurred along with this pathology. Aim: to assess the level of synthesis of cytokines and endometrial proteins in women with CE in the preconceptional stage and in the early stages of pregnancy; to identify pathogenetic aspects of the impact of imbalance of these substances on the processes of pregnancy loss; to assess the possibility of correcting the identifi ed changes in the preconceptional stage. Materials and methods. The study was conducted in 2 phases. In the fi rst phase, 426 women with CE were studied (168 patients (group I) were treated for CE in the preconception period, and the rest, 258 patients (group II), did not receive treatment). The control group consisted of 30 healthy women. The levels of cytokines TNF-a, INF-γ, and IL-10 in cervical mucus and glycodelin in menstrual blood were determined by enzyme- linked immunosorbent assay. In the second phase of the study, women who became pregnant were followed: 135 women from group I who received preconceptional treatment for CE; 168 women from group II who became pregnant along with untreated CE; and 20 healthy women from the control group who became pregnant and subsequently had no complications. At 5-6 weeks of gestation, serum glycodelin concentration and cervical content levels of TNF-a, INF-γ and IL-10 were determined. The data were processed using mathematical statistical methods, Student's t-test, Pearson's correlation coeffi cient (r) and odds ratio were evaluated using the STATISTICA program of StatSoft Inc. (USA). The study adhered to the tenets of the Declaration of Helsinki. The study protocol was approved by the local ethics committee of PSMU for all women enrolled in this study. The article is extracted from the initiative scientifi c research project of the Obstetrics and Gynecology Department No 2 of the Poltava State Medical University «Optimization of approaches to pregnancy management in women at high risk of obstetric and perinatal pathology» (term: 2022-2027; state registration number 0122U201228). Results and Discussion. At the preconceptional stage, patients with CE showed a signifi cant decrease in glycodelin levels by 2.9 times (p<0.05), an increase in proinfl ammatory cytokines (INF-γ by 2.8 times (p<0.001), TNF-α by half (p<0.001)), and a decrease in IL-10 by 2 times (p<0.001) compared to the levels in healthy non-pregnant women. A decrease in the level of glycodelin in menstrual blood of women with CE is inversely correlated with an increase in the level of proinfl ammatory cytokines in cervical mucus (both INF-γ; r= -0.77; p<0.05, and TNF-α; r= -0.69; p<0.05). At 5-6 weeks of gestation, the level of serum glycodelin was 14.5 % lower (р˂0.05) in patients with pregestational untreated CE and 58.6 % lower (p<0.001) in women with early pregnancy loss. The level of this protein in menstrual blood of women with CE before pregnancy was positively correlated with its concentration in serum at 5-6 weeks of pregnancy (r=0.61; p<0.01). Such a relationship was also characteristic for INF-γ (r=0.68; p<0.05) and TNF-α (r=0.78; p<0.05). An inverse correlation was also found between a decrease in glycodelin levels in the blood of pregnant women with a history of untreated CE at 5-6 weeks of pregnancy and an increase in TNF-α (r= -0.63; p<0.05) and INF-γ (r= -0.57; p<0.05) in the cervical mucus of these pregnant women at this stage of pregnancy. After treatment for CE, both in the preconceptional stage and in early pregnancy, an increase in glycodelin (р˂0.001), a decrease in INF-γ (p<0.05) and TNF-α (p<0.01), and an increase in IL-10 concentration (р˃0.05) were observed. The incidence of spontaneous abortion before 22 weeks' gestation decreased 1.9-fold in women who received preconception treatment (OR 2.79; CI 95 % [1.45-5.38]; p < 0.05). Conclusions. In women with CE, there is a decrease in glycodelin synthesis and cytokine imbalance with an increase in proinfl ammatory cytokines: INF-γ (2.8-fold; р˃0.001) and TNF-α (twofold; p<0.001). The preconceptional decrease in glycodelin synthesis correlates with a decrease in synthesis of this protein by decidual cells after pregnancy, as well as with the prevalence of INF-γ and TNF-α in early pregnancy in women with a history of CE. This sets the stage for impaired immune tolerance between the uterus and the fetus and is one of the leading causes of spontaneous abortion in women who become pregnant with untreated CE. Preconceptional treatment of CE prevents the formation of cytokine imbalance and increases glycodelin synthesis in the early stages of pregnancy, which protects the course of pregnancy and reduces the incidence of early preterm labor by 4.6 times.